Benzoimidazolium-derived dimeric and hydride n-dopants for organic electron-transport materials: impact of substitution on structures, electrochemistry, and reactivity - Mohapatra, Swagat K.; Al Kurdi, Khaled; Jhulki, Samik; Bogdanov, Georgii; Bacsa, John; Conte, Maxwell; Timofeeva, Tatiana V.; Marder, Seth R.; Barlow, Stephen (Beilstein Journal of Organic Chemistry, 2023)
1,3-Dimethyl-2,3-dihydrobenzo[d]imidazoles, 1H, and 1,1',3,3'-tetramethyl-2,2',3,3'-tetrahydro-2,2'-bibenzo[d]imidazoles, 12, are of interest as n-dopants for organic electron-transport materials. Salts of 2-(4-(dimethylamino)phenyl)-4,7-dimethoxy-, 2-cyclohexyl-4,7-dimethoxy-, and 2-(5-(dimethylamino)thiophen-2-yl)benzo[d]imidazolium (1g–i+, respectively) have been synthesized and reduced with NaBH4 to 1gH, 1hH, and 1iH, and with Na:Hg to 1g2 and 1h2. Their electrochemistry and reactivity were compared to those derived from 2-(4-(dimethylamino)phenyl)- (1b+) and 2-cyclohexylbenzo[d]imidazolium (1e+) salts. E(1+/1•) values for 2-aryl species are less reducing than for 2-alkyl analogues, i.e., the radicals are stabilized more by aryl groups than the cations, while 4,7-dimethoxy substitution leads to more reducing E(1+/1•) values, as well as cathodic shifts in E(12•+/12) and E(1H•+/1H) values. Both the use of 3,4-dimethoxy and 2-aryl substituents accelerates the reaction of the 1H species with PC61BM. Because 2-aryl groups stabilize radicals, 1b2 and 1g2 exhibit weaker bonds than 1e2 and 1h2 and thus react with 6,13-bis(triisopropylsilylethynyl)pentacene (VII) via a “cleavage-first” pathway, while 1e2 and 1h2 react only via “electron-transfer-first”. 1h2 exhibits the most cathodic E(12•+/12) value of the dimers considered here and, therefore, reacts more rapidly than any of the other dimers with VII via “electron-transfer-first”. Crystal structures show rather long central C–C bonds for 1b2 (1.5899(11) and 1.6194(8) Å) and 1h2 (1.6299(13) Å).
Keywords: benzoimidazole; crystal structure; kinetics; n-dopant; reduction